Ketoprofen-eluting biodegradable ureteral stents by CO₂ impregnation: In vitro study - Barros, A. A. (2015)
Ureteral stents are indispensable tools in urologic practice. The main complications associated with ureteral stents are dislocation, infection, pain and encrustation. Biodegradable ureteral stents are one of the most attractive designs with the potential to eliminate several complications associated with the stenting procedure. In this work we hypothesize the impregnation of ketoprofen, by CO2-impregnation in a patented biodegradable ureteral stent previously developed in our group. The biodegradable ureteral stents with each formulation: alginate-based, gellan gum-based were impregnated with ketoprofen and the impregnation conditions tested were 100 bar, 2 h and three different temperatures (35 °C, 40 °C and 50 °C). The impregnation was confirmed by FTIR and DSC demonstrated the amorphization of the drug upon impregnation. The in vitro elution profile in artificial urine solution (AUS) during degradation of a biodegradable ureteral stent loaded with ketoprofen was evaluated. According to the kinetics results these systems have shown to be very promising for the release ketoprofen in the first 72 h, which is the necessary time for anti-inflammatory delivery after the surgical procedure. The in vitro release studied revealed an influence of the temperature on the impregnation yield, with a higher impregnation yield at 40 °C. Higher yields were also obtained for gellan gum-based stents. The non-cytotoxicity characteristic of the developed ketoprofen-eluting biodegradable ureteral stents was evaluated in L929 cell line by MTS assay which demonstrated the feasibility of this product as a medical device.